(untitled) (Journal of Nobel Medical College, 2018)
Background: Pneumonia is the main cause of death among children under five years of age particularly in developing countries. According to the WHO, there are more than 15 million cases representing 7-13% of pneumonia cases annually which necessitate hospital admission due to their severity. There is paucity of data regarding the clinical spectrum and the epidemiology of severe pneumonia from eastern part of Nepal. It is important to understand the clinical spectrum and the epidemiology of severe pneumonia at local level to better define problem and to draw inferences for management and policy formulation. Material and Methods: A hospital based retrospective observational study conducted at Department of Pediatrics and Neonatology, Nobel Medical College and Teaching Hospital, Biratnagar, Nepal. One hundred and forty four cases with a diagnosis of severe pneumonia were studied over a period of one year. All the cases from 1 month to 5 years of age fulfilling the standard WHO case definition of severe pneumonia were included in the study. A pre-designed semi-structured questionnaire was used to obtain the clinical profile and investigations. Results: A total of 144 cases were studied and analyzed. The age range was from 1 month to 5 years. The mean age of the cases was 13.56 months. Majority of the cases belonged to age group of 1-6 months 40.27% (n=58). There was a male preponderance in our study comprising 58.3% (n=84) of males and 41.7% (n=60) of females. Fever and cough were the most common symptoms present in all cases, fever being present in 95.8% (n=136) cases and cough was present in 98.6% (n=142) cases. The most common radiological finding in our study was bronchopneumonia in 27.8% (n=40) cases followed by lobar pneumonia in 24.3% (n=35) cases and interstitial pneumonia in 18.8% (n=27) cases. Complications were present in 6.9% (n=10) cases and 22.2% (n=32) of the cases had no radiological abnormalities. Among the studied symptoms and signs of severe pneumonia, hurried breathing (p<0.001), wheeze (p=0.016), refusal of feeds (p=0.001), altered sensorium (p=0.006) and previous history of acute respiratory infections showed significant association with radiological abnormalities. Conclusion: Children of severe pneumonia presenting with fast breathing, wheeze, altered sensorium, refusal of feeding and past history of acute respiratory infections showed significant association with abnormal chest radiographs.